2010
DOI: 10.1021/bi901998m
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Combinatorial Screening of a Bacterial rRNA A-Site-like Motif Library: Defining Privileged Asymmetric Internal Loops That Bind Aminoglycosides

Abstract: RNAs have diverse structures that are important for biological function. These structures include bulges and internal loops that can form tertiary contacts or serve as ligand binding sites. The most commonly exploited RNA drug target for small molecule intervention is the bacterial ribosome, more specifically the ribosomal RNA aminoacyl-tRNA site (rRNA A-site) which is a major target for the aminoglycoside class of antibiotics. The bacterial A-site is composed of a 1×1 nucleotide all-U internal loop and a 2×1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 46 publications
1
33
0
Order By: Relevance
“…9,10,13,14 These studies found that selected interactions can occur with nanomolar K d 's to internal loops 9,10,13 and low micromolar K d 's to hairpin loops. 11,14 Aminoglycosides have a large number of amines and are therefore highly cationic ligands.…”
Section: Resultsmentioning
confidence: 95%
“…9,10,13,14 These studies found that selected interactions can occur with nanomolar K d 's to internal loops 9,10,13 and low micromolar K d 's to hairpin loops. 11,14 Aminoglycosides have a large number of amines and are therefore highly cationic ligands.…”
Section: Resultsmentioning
confidence: 95%
“…Excellent signal was still observed for all compounds. Subsequently, compounds PL-1 , HL-1 , HL-2 , and DL-1 were subjected to microarray-based selection using the oligonucleotides competitors described above (Figure 2) 20,21,48 . Three rounds of selection were completed prior to sequencing the RNA motifs that bind each ligand.…”
Section: Resultsmentioning
confidence: 99%
“…Microarrays were constructed as previously described 20,21,4856 . Compounds that were identified as hits from the dye-displacement assay were immobilized onto aldehyde-functionalized microarray via a reductive amination reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Similar specificities have been observed with aminoglycosides binding to RNA internal and hairpin loops when the RNAs have been selected to bind to aminoglycosides via 2DCS. (30, 48-51) Other studies have suggested that aminoglycoside recognition is shape-dependent. (47) The results presented here suggest that high affinity binding is also sequence dependent.…”
Section: Resultsmentioning
confidence: 99%